The Political aspects of Kazakh-Turkish Relations (1991-2007) (Journal of Oriental Studies, 2024)
In twenty five years, the Kazakh-Turkish political relations have growninto a strategic partnership. The strategic partnership is based on a stablepolitical relations. In this context, it is important to not be limited to theclassical concept of the alliance, but rather to analyze the political partnership between the two countries on the basis of a much deeper and morecritical concept of partnership. First of all, Kazakhstan and Turkey sharecommon historical roots and culture. This has contributed to a correct understanding of mutual political interests of the two countries and enhancement of the relationship to the level of a strategic partnership. Currently,both countries are strengthening the strategic partnership, basing manyissues in the Eurasian region on common political principles.Key words: Kazakhstan, Turkey, Russia, multilateral foreign policy,strategic partnership.